Low‐Invasive Cell Injection based on Rotational Microrobot. Issue 7 (1st April 2019) - Lu, Haojian; Yang, Yuanyuan; Lin, Xudong; Shi, Peng; Shen, Yajing
Abstract: The advancement of cell injections has created a need for accurate, efficient, and low‐invasive injections. However, the conventional approaches to reduce cell damage during penetration, mainly optimization of micropipette tips and vision‐based automatic injections, have almost reached the limit. Here, described are the design and implementation of a robotic‐aided rotatory microinjection system to reduce cell deformation and penetration force during the injection. The homocentric rotation technology integrates an ultraprecise manipulation system with multiple degrees of freedom, which tremendously diminishes the damage to the cell. Through systematic tests on zebrafish embryo microinjection, compared with traditional straightforward cell injection techniques, the rotary cell injection approach is able to reduce the penetration deformation and force of the specimen up to 30%. This work breaks the performance limit of current microinjection techniques, and paves a new way for the development of low‐invasive cell injection systems. It is envisioned that this rotary microrobot system can excavate enormous applications in the field of biomedicine, such as artificial fertilization and gene therapy. Abstract : The advancement of cell injection has created a need for accurate, efficient, and low‐invasive injections. This work describes the design and implementation of a robotic‐aided rotatory microinjection system to reduce cell deformation and penetration force during the injection, which is able to reduce the penetration deformation and force up to 30%.